Factors associated with new born care practice in Tarai districts of Lumbini province, Nepal: a cross-sectional study - Ruchal, R; Chhetri, P (Devdaha Medical Journal, 2026)
Introduction: Neonatal mortality remains a major public health concern, especially in low- and middle-income countries, with the first week of life being the most critical period. Limited postnatal care services and inadequate maternal knowledge and practices increase risks for newborns. This study aimed to assess factors associated with mothers’ knowledge and practices of newborn care among mothers with children less than one year in selected districts of Terai region of Lumbini province. Methods: A community-based cross-sectional study was conducted among 414 mothers with children age less than one year in three districts of the Lumbini province of Nepal using multistage proportionate random sampling. Data were analyzed in SPSS version 25 using descriptive statistics and logistic regression at p < 0.05. Results: Among the 414 respondents, 63.3% of mothers had adequate knowledge on newborn care, while 55.1% demonstrated good newborn care practices. Multivariable logistic regression analysis revealed that religion (p = 0.036), type of family (p < 0.001), parity (p = 0.039), husband’s education (p = 0.002), and monthly family income (p < 0.001) were significantly associated with mothers’ knowledge of newborn care. Similarly, parity (p = 0.041), maternal education (p = 0.002), and family income (p < 0.001) were significantly associated with newborn care practices. Conclusion: The majority of mothers had adequate knowledge and more than half practiced appropriate newborn care, however gaps still remain. Socio-demographic factors significantly influenced the level of mothers’ knowledge and practices. Strengthening maternal education and targeted health education programs may help to improve newborn care practices.